2021
DOI: 10.3390/ph14070690
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Effects of Anthocyanins in Human Health: A Comprehensive Review

Abstract: In recent years, the consumption of natural-based foods, including beans, fruits, legumes, nuts, oils, vegetables, spices, and whole grains, has been encouraged. This fact is essentially due to their content in bioactive phytochemicals, with the phenolic compounds standing out. Among them, anthocyanins have been a target of many studies due to the presence of catechol, pyrogallol, and methoxy groups in their chemical structure, which confer notable scavenging, anti-apoptotic, and anti-inflammatory activities, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
114
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(116 citation statements)
references
References 221 publications
1
114
0
1
Order By: Relevance
“…The beneficial antioxidant, anti-inflammatory, neuroprotective, immunomodulating and adaptogenic effect of the molecules examined in our study was demonstrated on the retina, vitreous and ocular surface [26]. Previous studies [27][28][29] have shown that dietary modifications and dietary supplements can be used to prevent and/or treat ocular surface conditions.…”
Section: Discussionsupporting
confidence: 56%
“…The beneficial antioxidant, anti-inflammatory, neuroprotective, immunomodulating and adaptogenic effect of the molecules examined in our study was demonstrated on the retina, vitreous and ocular surface [26]. Previous studies [27][28][29] have shown that dietary modifications and dietary supplements can be used to prevent and/or treat ocular surface conditions.…”
Section: Discussionsupporting
confidence: 56%
“…The strong anti-cancer effects of anthocyanins are intimately linked to their catechol, pyrogallol, and methoxy groups present in their chemical structure, which confer them notable antioxidant, anti-cancer, antimutagenic and anti-inflammatory effects, including the capacity to (i) interfere with ERK, JNK, MAPK, NF-κB and PI3K/Akt pathways, (ii) arrest cells proliferation in G1/S and G2/M phases, (iii) activate the caspase cascade, (iv) increase intracellular antioxidant enzymes, (v) modulate aromatase activity, (vi) regulate estrogenic/antiestrogenic levels, (vii) reduce mitochondria membrane potential and (viii) inhibit procarcinogens activation by interfering with phase I metabolizing enzymes, such as cytochrome P450 [11,[56][57][58][59][60].…”
Section: Effect Of Sweet Cherry Fractions In Hepg2 Cell Viabilitymentioning
confidence: 99%
“…Owing to rich hydroxyl groups in their chemical structures, anthocyanins also represent one of the largest families of phenolic pigments with antioxidant and anti-inflammatory properties ( 16 ). Habitual consumption of anthocyanins and anthocyanin-rich foods was suggested to reduce the risks of various chronic diseases including CVD, neuroinflammatory process, and liver steatosis ( 17 ). A previous meta-analysis of prospective studies found that frequent intake of anthocyanin-rich foods was related to 9% lower risk of coronary heart disease (CHD) ( 18 ).…”
Section: Introductionmentioning
confidence: 99%